DESAIN DAN REALISASI ACCELEROMETER BERBASIS ARDUINO SEBAGAI INSTRUMEN PENDETEKSI MIKROTREMOR - Ahmad Amiruddin; Suharno Suharno; Karyanto Karyanto (Jurnal Geofisika Eksplorasi, 2019)
To investigate soil vulnerability zones, one of the methods is microtremor analysis to analyze soil characteristics based on the natural frequency of the soil layer. However, the technology used to obtain the data is still expensive. Considering the need for this technology, this research was conducted to design a tool used as a microtremor analysis with Arduino-based accelerometer which is affordable and easier to use.  As a result, the design of the accelerometer body size is 18.5 cm x 12 cm x 7 cm with the bottom side of the box made of the iron plate as a vibration medium and the lid box is made of mica. The program system can work efficiently with a maximum sampling rate of data collection of 500/s. From the validation test, the f0 value of the HVSR curve from the accelerometer tool ranges from 0.19 Hz - 0.93 Hz. Whereas from the reference tool Reftek Accelerograph produces a range of 0.18 Hz - 0.90 Hz. The smallest difference between the two measurement tools is 0.0072 Hz at point 1 and the biggest difference is 0.1299 Hz at point 3. The average difference between the two values of f0 is 0.0377 Hz.